Burnout syndrome in the Czech Republic: The decreasing trend over the years - Vňuková, Martina Sebalo; Sebalo, Ivan; Brečka, Tibor; Anders, Martin; Ptáček, Radek (Frontiers in Public Health, 2023)
Introduction Burnout syndrome is a state of long-term work exhaustion that manifests on three levels: cognitive, physical and emotional. This study examines trends in burnout in the Czech population. The main aim of this research was to fill in the burnout literature gap and document the burnout trend over the years. Our secondary aim was to see if there is awareness regarding burnout syndrome and whether, over the years, we will see an increasing or a decreasing trend in burnout prevalence. Methods Data collection took place in three waves using the computer assisted web interviewing (CAWI) method. In 2014 n = 1027, in 2017 n = 1024 and in 2020 Nn= 1000. Respondents were selected from the European National Panel. Because the target group was adults (18-65 years), an online survey was chosen. Internet penetration in this target population is sufficient, and it was not necessary to use a combination of methodologies. Results The results suggest a decreasing tendency for burnout syndrome in the Czech Republic. Knowledge about burnout syndrome is increasing, suggesting that people are paying more attention to their mental health and the possible factors that might affect the severity of burnout syndrome. Conclusion Overall, burnout threatens the general population, not only medical employees. It is a positive finding that over the years, there has been an increasing trend in awareness about burnout. It further shows that people have adopted certain precautions and steps to avoid burnout syndrome as the perceived threat from it gradually decreases.